A Rare Complication of ERCP - Gökbulut, Volkan; Ödemiş, Bülent; Öztürk, Ömer; Yamak, Bülent; Tenlik, İlyas and Abaylı, Selcen Yüsra and Öztürk, Handan (Turkish Journal of Gastroenterology, 2022)
Cite this article as: Gökbulut V, Ödemiş B, Öztürk Ö, et al. A rare complication of ERCP. Turk J Gastroenterol. 2022;33(4):365-367.